2016
DOI: 10.25077/jka.v5i2.536
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Pasien Tonsilitis Kronis pada Anak di Bagian THT-KL RSUP Dr. M. Djamil Padang Tahun 2013

Abstract: AbstrakTonsilitis Kronis merupakan penyakit yang paling sering terjadi diantara semua penyakit tenggorok terutama pada anak.  Penyakit ini terjadi karena adanya serangan lanjutan pada tonsil yang telah mengalami peradangan sebelumnya yang disebabkan oleh virus atau bakteri.Tonsilitis Kronis menempati urutan kedua tertinggi penyakit THT di Indonesia. Tujuan penelitian ini adalah mengetahui karakteristik tonsilitis kronis pada anak  di Bagian THT-KL RSUP Dr. M. Djamil Padang. Penelitian ini bersifat deskriptif d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The results of this study are in line with previous research conducted by Fakh, in the ENT-KL Section of RSUP Dr. M. Djamil Padang also found that most of the sexes of patients with tonsillitis were women (56%). 20 Research conducted by Kishveet al conduct researchcase series in India, out of 203 tonsillitis patients with the majority aged 5-14 years, more were female, namely 105 (51.72%), while men were 98 (48.28%). 21 This is in accordance with data from the prevalence of chronic diseases in the United States, it was found that the average number of chronic tonsillitis sufferers each year is more in the female sex, namely 13.7/1,000 population while men are as much as 9/1,000 population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with previous research conducted by Fakh, in the ENT-KL Section of RSUP Dr. M. Djamil Padang also found that most of the sexes of patients with tonsillitis were women (56%). 20 Research conducted by Kishveet al conduct researchcase series in India, out of 203 tonsillitis patients with the majority aged 5-14 years, more were female, namely 105 (51.72%), while men were 98 (48.28%). 21 This is in accordance with data from the prevalence of chronic diseases in the United States, it was found that the average number of chronic tonsillitis sufferers each year is more in the female sex, namely 13.7/1,000 population while men are as much as 9/1,000 population.…”
Section: Resultsmentioning
confidence: 99%
“…16 341 (42%) with tonsil size T3 and a study conducted by Fakh 2013 also obtained tonsil size results in children which were most commonly found in this study, namely T3 -T3 sizes (68%). 20 One of the factors for enlargement of the tonsils is due to the influence of infection in the tonsils. Enlarged tonsils due to parenchymal hyperplasia or fibrinoid degeneration with obstruction of the tonsillar crypts.…”
Section: Resultsmentioning
confidence: 99%
“…Tonsilitis kronis adalah peradangan tonsil yang menetap sebagai akibat infeksi akut atau subklinis yang berulang yang dapat mengakibatkan kerusakan permanen pada tonsil atau kerusakan ini juga dapat terjadi jika pengobatan yang dilakukan tidak adekuat. Selain pengobatan tonsilitis akut yang tidak adekuat, faktor predisposisi timbulnya tonsilitis kronis lain adalah higien mulut yang buruk, kelelahan fisik dan beberapa jenis makanan (Fakh, Novialdi, & Elmatris, 2016) Jenis makanan yang tidak baik bisa menyebabkan tingginya progresifitas tonsillitis. Kebiasaan mengkonsumsi makanan cepat saji (fast food) yang mengandung minyak, penyedap rasa seperti MSG (Mono Sodium Glutamat) dan mengandung bahan pengawet apabila di konsumsi secara berlebihan akan menimbulkan gejala rasa gatal Hubungan Kebiasaan Mengkonsumsi Makanan Cepat Saji Dengan Kejadian Gejala Tonsilitis Kronik Pada Mahasiswa Fakultas Kedokteran Universitas Yarsi Angkatan 2021 Dan Tinjauannya Menurut Pandangan Islam ataupun sakit pada tenggorokan sehingga menyebabkan peradangan pada tonsila palatina .…”
unclassified